On the perceptually irrelevant phase information in sinusoidal representation of speech. - Doh-Suk Kim (IEEE Transactions on speech and audio processing)
For efficient quantization of speech representations, it is essential to incorporate perceptual characteristics of human hearing. However, the focus has been confined only to the magnitude information of speech, and little attention has been paid to phase information. This paper presents a novel approach, termed perceptually irrelevant phase elimination (PIPE), to find out irrelevant phase information in acoustic signals in terms of perceived quality. The proposed method, inspired by the observation that the relative phase relationship within a critical band is perceptually important, is derived not only for stationary Fourier signals but also for harmonic signals. For harmonic signals, the "critical phase frequency" is defined below which phase information is perceptually irrelevant. The PIPE algorithm is incorporated into the harmonic analysis/synthesis of speech, and subjective test results demonstrate the effectiveness of the proposed method